2007
DOI: 10.1007/s10038-007-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of genetic variants in IL23R, ATG16L1 and 5p13.1 loci with Crohn’s disease in Japanese patients

Abstract: Inflammatory bowel diseases, Crohn's disease (CD) and ulcerative colitis are characterised by chronic transmural, segmental and typically granulomatous inflammation of the gut. Each has a peak age of onset in the second to fourth decades of life and prevalence has been increasing significantly in both Western countries and Japan over the last decade, while their pathogenesis remains largely unknown. Recently, positive association of CD with the variants in interleukin 23 receptor (IL23R), autophagyrelated 16-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 36 publications
10
153
5
Order By: Relevance
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in a very recent study McCarroll et al 56 have shown that the causal variant responsible for IRGM Figure 1 Pooled data for the ATG16L1 rs2241880 susceptibility allele frequency (SAF). (a) Pooled data of Australian, 39 Belgian, 16 British, 14,21,23,25 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 27,33 Hungarian, 34 Japanese, 22 New Zealander, 26 North American 15,24 and Spanish cohorts for Crohn's disease (CD). (b) Pooled data of Australian, 39 British, 21,23,37 Canadian, 31 Dutch, 28 German, 14,29,30 Italian, 33 Hungarian, 34 New Zealander, 26,39 North American 15 and Spanish cohorts for ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][21][22][23][24][25][26][27][28][29][30][31][32][33][34]38,39 Funnel plots and Egger tests were performed to analyse the publication bias of the meta-analysis. No statistically significant values were observed in CD studies (P ¼ 0.6) or UC studies (P ¼ 0.4), with symmetric funnel plots for both studies (Supplementary Figure 1).…”
Section: Association Of Atg16l1 and Irgm With Ibd Rj Palomino-moralesmentioning
confidence: 99%
See 1 more Smart Citation
“…57,60,68 Nevertheless, the described ATG16L1 association with Crohn disease has not been observed in any Asian meta-analyses. [69][70][71] The rs2241880 variant can be observed in all isoforms of ATG16L1 72 and comprises a nonsynonymous coding SNP (adenine (A) ! guanine (G) polymorphism) in the coiled-coil domain encoding a threonine-to-alanine substitution.…”
Section: Atg16l1 and Susceptibility To Crohn Diseasementioning
confidence: 99%
“…Strong association also was observed with rs11465817 (p = 1.2 x 10 -10 ), compared with rs11209026 (p = 2.3 x 10 -9 ). Among East Asians, IL23R is not associated with Crohn's disease (CD) in Japanese 10 , nor with psoriasis in Han Chinese 11 or AS in Koreans 12 or Han Chinese 13 .…”
Section: Non-mhc and As Susceptibilitymentioning
confidence: 99%